Propolis encapsulation by spray drying: Characterization and stability - Busch, Verónica María (2017)
Propolis extracts have shown to possess several health beneficial properties attributed to their phenol composition. Several pharmaceutical formulations are based on propolis as active ingredient and it could also be a potential component of functional foods. The main drawback for its application as food ingredient is its low water solubility, strong taste and aroma. In this work, an encapsulated Argentine alcohol-free propolis powder was obtained by spray drying, by using different maltodextrin matrices, with or without added gums. Besides, physicochemical characterization of powders and biocompound stability studies towards humidification at different water activities were done. Galangin and pinocembrin were the major components identified by HPLC in propolis before and after the drying process. The SEM images analysis showed that the addition of gums improved the particles integrity and size homogeneity. Furthermore, a higher degree of encapsulation of some polyphenols (such as quercetin), higher antioxidant activity measured by the reducing power assay, and higher physical stability toward humidification and physical collapse were also achieved especially in gum-added systems. The use of propolis as an encapsulated powdered additive widens its alcohol-free dosage applications.